2008
DOI: 10.1017/s0007114507824123
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Fatty acids and mood: the devil is in the detail

Abstract: Increasing evidence suggests that a low dietary intake of the n-3 long-chain PUFA EPA and DHA may contribute not only to the risks for various physical illnesses (particularly cardiovascular and immune system disorders), but also to many disorders of mental health and performance1,2. From their recent comprehensive review of the evidence for these n-3 fatty acids in the prevention and treatment of psychiatric disorders3, the American Psychiatric Association (APA) made the following recommendations:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…A third meta-analysis found evidence of efficacy in major depression, but no evidence of efficacy in depressed mood [Appleton et al, 2006], similar to later RCT by the same authors who concluded that supplementation with 1.7 g DHA + EPA was not efficacious in correcting mild to moderate depression [Rogers et al, 2008]. The metaanalysis has been criticized for over-inclusiveness [Richardson, 2008].…”
Section: Lcpufa and Depression In Men And In Non-pregnant And Non-lacmentioning
confidence: 67%
“…A third meta-analysis found evidence of efficacy in major depression, but no evidence of efficacy in depressed mood [Appleton et al, 2006], similar to later RCT by the same authors who concluded that supplementation with 1.7 g DHA + EPA was not efficacious in correcting mild to moderate depression [Rogers et al, 2008]. The metaanalysis has been criticized for over-inclusiveness [Richardson, 2008].…”
Section: Lcpufa and Depression In Men And In Non-pregnant And Non-lacmentioning
confidence: 67%
“…However, another meta-analysis did not support the antidepressant effects of n-3 PUFAs when heterogeneous populations (e.g. community samples) were included [28,29] ; the negative finding needs to be interpreted with caution because of a few limitations such as pooling heterogeneous populations, using different mood assessments, and implementing different intervention methods [30] . In addition, the active component of the antidepressant effect in n-3 PUFAs is still unknown, although it has been argued that EPA might be more effective than DHA [23] .…”
Section: Role Of N-3 Pufas In Depressionmentioning
confidence: 99%
“…DHA is commonly believed to be the key element for mental health as it is an essential component of neuronal membranes and thus critical to the structure of the brain and nervous system, while EPA is believed to have direct interactions with cyclo-oxygenases, lipoxygenases, phospholipases, acylating systems, ion channels, mitochondria, and the peroxisome proliferator activated receptors. It is also thought to exert regulatory influences on gene expression [39][40][41]. Nevertheless, more studies are needed to better understand the role of these FAs in CV disease and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Results of meta-analyses indicate that omega-3 FA supplement is beneficial for patients who have a formal diagnosis of depression [56]. Variation of dosing and proportion of omega-3 FA supplement have been speculated to be responsible, at least partially, for the inconsistent findings of benefits in depression and many other conditions [39,40,55]. While Lovaza (similar EPA to DHA concentrations) failed to demonstrate antidepressant effects [57], an almost pure EPA supplement demonstrated antidepressant efficacy [58].…”
Section: Discussionmentioning
confidence: 99%